2018
DOI: 10.3389/fvets.2017.00247
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Mycobacterium bovis Infection: the Badger Model As a Paradigm for Understanding Tuberculosis in Animals

Abstract: Tuberculosis in animals is caused principally by infection with Mycobacterium bovis and the potential for transmission of infection to humans is often the fundamental driver for surveillance of disease in livestock and wild animals. However, with such a vast array of species susceptible to infection, it is often extremely difficult to gain a detailed understanding of the pathogenesis of infection--a key component of the epidemiology in all affected species. This is important because the development of disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 93 publications
(113 reference statements)
1
35
0
Order By: Relevance
“…As could be expected [ 20 , 38 ], these experimental results suggest that depending on the route of infection the distribution of lesions can vary; that is, after an endotracheal challenge, lesions are more likely to be found in the respiratory tract and associated tissues whereas the digestive tract is the most affected area after an oral challenge. Although the number of animals used was small, these findings are consistent with the results obtained in previous studies where it was stated that after inhalation of M. bovis most lesions appear in the nasopharynx and lower respiratory tract, including the lungs and associated LN and that M. bovis ingestion usually causes lesions in the mesenteric lymph nodes [ 17 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As could be expected [ 20 , 38 ], these experimental results suggest that depending on the route of infection the distribution of lesions can vary; that is, after an endotracheal challenge, lesions are more likely to be found in the respiratory tract and associated tissues whereas the digestive tract is the most affected area after an oral challenge. Although the number of animals used was small, these findings are consistent with the results obtained in previous studies where it was stated that after inhalation of M. bovis most lesions appear in the nasopharynx and lower respiratory tract, including the lungs and associated LN and that M. bovis ingestion usually causes lesions in the mesenteric lymph nodes [ 17 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 81%
“…There is a general acceptance that the aerogenous transmission is the most frequent one in cattle and lesions are usually found in the respiratory system and associated lymph nodes (LN) [ 17 , 18 ]. This also seems to be the case for natural intra-species transmission in the badger, the principal wild animal reservoir in Ireland and UK [ 20 ]. Lesions can also reach these LN and other tissues or LN of the head region [ 17 , 18 , 21 ] after oral exposure to M .…”
Section: Introductionmentioning
confidence: 99%
“…A study on the accuracy of histopathological techniques was carried out on limited number of samples from cattle with classical histology features of tuberculosis by Virieux, 2006. The accuracy of histopathologic techniques on large number of samples is available only in cervids (Gormley and Corner, 2018). Varello et al, 2008 claimed that histopathology demonstrated high sensitivity (93.4%) and specificity (92.3%), while ZN sensitivity and specificity were respectively 33.9 and 100 per cent.…”
Section: Histologic Features Comprised a Classic Granuloma As A Charamentioning
confidence: 99%
“…Tuberculosis is caused by Mycobacterium tuberculosis in humans resulting in active TB (6) in and M. bovis in cattle with a broader host range for TB in domestic and wild animals (7,8). In addition, M. bovis infects humans, causing zoonotic TB in humans (9).…”
Section: Introductionmentioning
confidence: 99%